Delayed Presentation of Popliteal Artery Injury after Salter-Harris III Proximal Tibia Fracture - Alexandra H. Seidenstein; Timothy W. Torrez; Jacob A. Garcia; Shadi K. Awad; Henry Debell; Shawn R. Gilbert; Kevin A. Williams (Case Reports in Orthopedics, 2023)
Introduction. Proximal tibia physeal fractures in children are not very common but can be dangerous because they can harm popliteal fossa structures, especially the popliteal artery. Popliteal artery injuries (PAI) are most commonly the result of trauma to the lower extremity, including blunt force, hyperextension injuries, complex fractures, and knee dislocations that can compromise popliteal neurovascular structures. Case Presentation. A 14-year-old boy presents to the emergency department after being transferred from an outside hospital 24 hours after a left lower extremity hyperextension injury. Radiographs demonstrated a Salter-Harris III proximal tibia fracture with posterior displacement. ABIs were deferred due to palpable distal pulses and no evidence of compartment syndrome. Closed reduction and percutaneous pinning were planned to correct the fracture. Intraoperatively, it was discovered that knee extension decreased lower extremity perfusion while knee flexion returned perfusion. An angiography revealed a popliteal artery occlusion with no distal flow. Based on this, an above-knee to below-knee popliteal bypass using the contralateral great saphenous vein was performed followed by closed reduction and percutaneous pinning of the proximal tibia. Conclusion. Proximal tibia physeal injuries, especially the Salter-Harris III and IV injuries, warrant a high index of suspicion of popliteal artery injuries. Palpable pulses and delayed presentation in the distal lower extremity do not rule out a PAI because collateral flow to the anterior and posterior tibial arteries may mask signs of an avascular limb, highlighting the need for a thorough history and physical exam. The authors present this case to reaffirm the importance of an ankle-brachial index when evaluating hyperextension injuries with proximal tibial epiphyseal fractures.